Emerging Hardware Technologies and 3D System Integration for Ubiquitous Machine Intelligence - Li, Haitong (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
Next-generation semiconductor hardware technologies and system integration serve as the physical foundation in the pursuit of ubiquitous machine intelligence, with unprecedented requirements in energy efficiency, performance, cost effectiveness, and security. Here, we provide an overview of emerging technologies with an emphasis on 3D system integration, and discuss on cross-layer designs for memory-centric computing in the 3D era.